Corticosterone regulates both naturally occurring and cocaine‐induced dopamine signaling by selectively decreasing dopamine uptake. (6th November 2017) - Wheeler, Daniel S.; Ebben, Amanda L.; Kurtoglu, Beliz; Lovell, Marissa E.; Bohn, Austin T.; Jasek, Isabella A.; Baker, David A.; Mantsch, John R.; Gasser, Paul J.; Wheeler, Robert A.
Abstract: Stressful and aversive events promote maladaptive reward‐seeking behaviors such as drug addiction by acting, in part, on the mesolimbic dopamine system. Using animal models, data from our laboratory and others show that stress and cocaine can interact to produce a synergistic effect on reward circuitry. This effect is also observed when the stress hormone corticosterone is administered directly into the nucleus accumbens (NAc), indicating that glucocorticoids act locally in dopamine terminal regions to enhance cocaine's effects on dopamine signaling. However, prior studies in behaving animals have not provided mechanistic insight. Using fast‐scan cyclic voltammetry, we examined the effect of systemic corticosterone on spontaneous dopamine release events (transients) in the NAc core and shell in behaving rats. A physiologically relevant systemic injection of corticosterone (2 mg/kg i.p.) induced an increase in dopamine transient amplitude and duration (both voltammetric measures sensitive to decreases in dopamine clearance), but had no effect on the frequency of transient release events. This effect was compounded by cocaine (2.5 mg/kg i.p.). However, a second experiment indicated that the same injection of corticosterone had no detectable effect on the dopaminergic encoding of a palatable natural reward (saccharin). Taken together, these results suggest that corticosterone interferes with naturally occurring dopamine uptake locally, and this effect is a critical determinant of dopamine concentration specifically in situations in which the dopamine transporter is pharmacologically blocked by cocaine. Abstract : We examined the effect of corticosterone on spontaneous dopamine release events (transients) in the NAc core and shell in behaving rats. Corticosterone increased dopamine transient amplitude and duration (measures sensitive to decreases in dopamine clearance), but had no effect on the frequency of transient release events. This effect was compounded by cocaine. These results suggest that corticosterone acts synergistically with cocaine to interfere with naturally occurring dopamine uptake.